Developing Mathematical Literacy Using the Ramayana Ballet Context with Indonesian Realistic Mathematics Education - Gunawan, Monica Tiara; Julie, Hongki; Rudhito, Marcellinus Andy; Kristianto, Yosep Dwi (Jurnal Pendidikan Matematika (JUPITEK), 2025)
This article emphasizes the importance of the PMRI and ethnomathematics for meaningful learning. In addition, low mathematical literacy is caused by students’ difficulties in connecting concepts with real-life contexts, while the integration of cultural contexts such as the Ramayana Ballet into PMRI remains limited. This study aims to (1) design and implement Hypothetical Learning Trajectory (HLT) with PMRI and LKPD with Ramayana Ballet Prambanan context to develop mathematical literacy skills, (2) describe students' mathematical literacy skills after experiencing learning on circle topic with PMRI. The type of research used is design research with stages (1) designing HLT, (2) implementing HLT, and analyzing students' mathematical literacy skills after experiencing learning. The data analysis technique used was reducing data, presenting data, and drawing conclusions. The results obtained were: (1) Mathematics learning in class VIII Pinisi effectively brought up all the characteristics of PMRI; and (2) Mathematical literacy skills of students in class VIII Pinisi after learning with the PMRI showed that students still had difficulties in several aspects, namely: (a) problem 1, writing complete information (level knowing), (b) problem 2, writing complete information, applying strategies and operations for problem solving (level applying), and (c) problem 3, providing mathematical arguments and assessing problem solving strategies and alternative solutions (level reasoning).